Multi-Omics Research Reveals the Effects of the ABA-Regulated Phenylpropanoid Biosynthesis Pathway on the UV-B Response in Rhododendron chrysanthum Pall. - Wang Yu; Xiangru Zhou; Jinhao Meng; Xiaofu Zhou; Hongwei Xu (Plants)
The growing depletion of the ozone layer has led to increased ultraviolet B (UV-B) radiation, prompting plants like the alpine Rhododendron chrysanthum Pall. (R. chrysanthum) to adapt to these harsh conditions. This study explored how abscisic acid (ABA) signaling influences R. chrysanthum’s metabolic responses under UV-B stress. R. chrysanthum was treated with UV-B radiation and exogenous ABA for widely targeted metabolomics, transcriptomics, and proteomics assays, and relevant chlorophyll fluorescence parameters were also determined. It was observed that UV-B stress negatively impacts the plant’s photosynthetic machinery, disrupting multiple metabolic processes. Multi-omics analysis revealed that ABA application mitigates the detrimental effects of UV-B on photosynthesis and bolsters the plant’s antioxidant defenses. Additionally, both UV-B exposure and ABA treatment significantly influenced the phenylpropanoid biosynthesis pathway, activating key enzyme genes, such as 4CL, CCR, and HCT. The study also highlighted the MYB–bHLH–WD40 (MBW) complex’s role in regulating this pathway and its interaction with ABA signaling components. These findings underscore ABA’s crucial function in improving plant resistance to UV-B stress and offer novel insights into plant stress biology.